A "Special Ambience" for Fashion and Tourism: from Capri to Positano - Cirillo, Ornella (ZoneModa Journal, 2021)
The identification of many places as centres of designer shopping has in recent decades favoured a number of Italian destinations for which this aspect has become a promotional feature similar to art, landscape and food. In Campania, this phenomenon has developed particularly in Capri, Ischia and Positano, wherein the mid-twentieth century, thanks to the initiative of local craftsmen or cunning outsiders, tailor’s shops, boutiques and workshops were set up in response to customers’ demand for clothes and accessories suited to holiday life. Thus, for different reasons and in different ways, resort fashion has taken off here, a thriving national production sector, characterised by accents strongly related to the ‘knowledge’, rituals and climate of these special places. The combination of the intangible qualities which characterised the garments and the craft traditions of the localities gave rise to artefacts capable of responding to the search for new emotional sensations that belonged to the steadily increasing number of tourists, which was satisfied by environments and lifestyles that were completely different from their usual ones. This process found a decisive conjuncture in the fact that in the middle of the century fashion joined tourism and cinema to bring Italy out of the post-war crisis. And in Campania, in particular, manufacturing and cultural conditions, folklore and the rich natural heritage of the coasts were some of the main drivers of this project, favoured in this sense in Capri and Positano by ideal landscape conditions for conveying the results of the most authentic creativity.